KARAKTERISTIK SOSIAL EKONOMI KELUARGA YANG ISTRINYA BEKERJA SEBAGAI BURUH INDUSTRI ROTI SURYA MODERN BAKERY - Ria Siti Nur Hasanah; Budiyono Budiyono; Edy Haryono (JPG (Jurnal Penelitian Geografi), 2013)
The aim of this research was to find out the socio-economic characteristics of the family whose wife works as labour in Surya Modern Bakery at Purwodadi Village, Trimurjo District, Central Lampung in the year of 2012. The research focused on: the age, education level, working hours, working time, number of children, wages, and the contributions to the fulfillment of the minimum requirements in the family. In this research, the researcher used descriptive method. The population in this research were 103 laborers, were taken 40% of sample (41 labours). The data collecting techniques of the research were observation, structured interviews and documentation. As data analysis, the researcher used cross-tabulations and percentage as the basis of description and interpretation in the making of this research report. The results of this research indicated that: (1) There were 90,2% of productive laborers and the difference in age did not affect on the wages. (2) The difference of laborers’ education level did not differentiate the wages. (3) All of the laborers had evenly high working hours. (4) The packing laborers’ working time differentiated the wages because of the skills they had. But, the wages for production laborers were not different. (5) On average, the number of laborers’ children were 3 children/family, the least were 1 child/family and the most were 10 children/family. (6) The total income of the wife who worked as laborer (Rp 21,508,000/month) had contributed 41% of the total family income (Rp 64,358,000/month). (7) The fulfillment of the minimum requirements in the family before the wife worked as laborer was 48,8% and it improved to 90,2% after the contribution of the wife who had worked. Key words : Socio-economic characteristics, wife, labour